PENERAPAN COLLABORATIVE GOVERNANCE DALAM PROGRAM PENCEGAHAN STUNTING DI KOTA PEKANARU TAHUN 2023 - Octaviana, Lilis; Zebua, Ben Hansel Notatema (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Stunting is a public health problem that impacts the quality of future human resources and therefore requires multi-stakeholder intervention. This study aims to analyze the implementation of collaborative governance in the stunting prevention program in Pekanbaru City in 2023. The study used a descriptive qualitative approach with data collection techniques through interviews and documentation. The analysis utilized Ansell and Gash's collaborative governance theory, which encompasses initial conditions, facilitative leadership, institutional design, and collaboration processes. The results indicate that collaborative governance in stunting prevention in Pekanbaru City has been implemented through the Foster Parents and Stunting Children (BAAS) Program, involving the Pekanbaru City Government, the National Population and Family Planning Board (BKKBN), the Health Office, the private sector such as PT Pertamina Hulu Rokan (PHR), and the community. The study concluded that collaborative governance in the stunting prevention program in Pekanbaru City in 2023 has been implemented but has not yet been optimally implemented. Stronger regulations are needed to ensure sustainable and effective collaboration in reducing stunting rates. Keywords: Collaborative Governance, Stunting Prevention, Pekanbaru